La nouvelle économie des ressources et les marches de l'eau : une perspective idéologique ? - Olivier Petit (VertigO)
TheNew Resource Economics perceives market allocation as a universal solution to resource depletion. The authors of this school are arguing for of a systematic implementation of private property rights concerning the allocation of renewable natural resources, because of the so-called “efficiency” of market mechanisms. But, as we show, they use an argumentation both inductive and historicist. Thus, this article studies the discourse of the New Resource Economics in the field of water resources in order to demonstrate that their point of view is largely ideological.